PENGARUH CITRA MEREK, HARGA, DAN KEPERCAYAAN TERHADAP MINAT BELI KONSUMEN PADA LAYANAN ONLINE TRAVELOKA - Arimbi, Isti Fauzia; Heryenzus, Heryenzus (LPPM Universitas Putera Batam, 2019)
Traveloka is the fastest, cheapest and most comprehensive airline ticket search site. The prices displayed on the Traveloka website have been processed from a network of official sources. The purpose of this study was to determine the effect of brand image, price, and trust in consumer buying interest in Traveloka Online services. The population in this study are consumers who have used Traveloka Online services. The number of samples in this study were 100 respondents with a simple random sampling technique. The data analysis technique in this study uses multiple linear regression analysis, classical assumption test, statistical test. The results of this study indicate that brand image, price, and trust simultaneously have a significant effect on buying interest in Traveloka Online services. Partially the brand image and price do not significantly affect the interest in buying Traveloka Online services and Trust partially significantly affects buying interest in Traveloka Online services. In implementing the marketing strategy, it further increases trust, given that consumer trust in traveloka has not been well embedded. This can be done for example by way of making the design more interesting, easy to understand, and responsible for every problem.